Fixed-Time-Synchronized Consensus Tracking of Multi-agent Systems - Jiang, Yulong; Hu, Wenfeng (2022 5th International Conference on Intelligent Autonomous Systems (ICoIAS), 2022)
This paper investigates the fixed-time-synchronized consensus tracking problem for multi-agent systems with undirected topology. A nonlinear distributed control law for first-order multi-agent systems is proposed based on norm-normalized sign function, with which all the elements of all the agents' states track the leader's state at the same time and in fixed time. Then, the corresponding results are extended to second-order multi-agent systems by adopting the terminal sliding mode control method. Finally, numerical simulations are performed to verify the theoretical results in this paper.